Out of sight out of mind: Psychological distance and opinion about the age of penal majority - Caldas, Ivete Furtado Ribeiro; Paim, Igor de Moraes; Leite, Karla Tereza Figueiredo; de Mello Junior, Harold Dias; Bataglia, Patrícia Unger Raphael [UNESP]; Martins, Raul Aragão [UNESP]; Pereira, Antonio (Frontiers, 2022)
The growth of urban violence in Brazil, as in other countries, has led citizens to demand more severe and punitive measures to solve the problem of juvenile crime. One motion submitted to the Brazilian parliament, for instance, proposes to reduce the age of penal majority (APM) from 18 to 16 years. Our hypothesis is that popular opinions about this proposal are largely constrained by construal levels and psychological distance. Accordingly, we expect that the knowledge and proximity to the circumstances associated with juvenile transgression will influence opinions about the proposal. To test this hypothesis, we evaluated how opinion against or for the proposal can be explained by psychological distance and moral development theory. We studied two samples, composed of people who do not have a deep experience with the subject (passersby in a public square (N = 77) and workers from a juvenile justice court (N = 157). After collecting socio-demographic information from the subjects and their answer to moral dilemmas, the data was subjected to a multivariate analysis by multimodal logistic regression for socio-demographic characteristics, Kohlberg moral stages, and opinion on the reduction of APM (agree, indifferent, and disagree) as dependent variables. Our findings suggest that 1) opinion about the APM depends on psychological distance and 2) socioeconomic variables may influence the average construal level of adolescent transgressors in the public’s perspective.
Keywords: adolescence; moral development; psychological distance; public opinion; youth justice